ELEMENTARY EDUCATION AT THE DAWN OF THE INDEPENDENCE WITHIN AN IBEROAMERICAN CONTEXT - Torres Aguilar, Morelos (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The article is the result of an investigation into the teaching of the first letters in Chiapas, in the aftermath of the colony and during the revolution of independence. The work contextualizes and examines the educational discourse of colonial regime, and compares it to similar efforts that took place in Spain and other countries in Latin America. Of the sources consulted, it concludes that they failed the efforts made by the Spanish Crown in teaching first letters addressed to the population in general.